PERSEPSI DAN FAKTOR PSIKOLOGIS DALAM PENGAMBILAN KEPUTUSAN HUTANG - Supramono Supramono; Nancy Putlia (University of Merdeka Malang, 2010)
The f inance literature supported an increasing role for psychological aspects inthe context of f inancial decision making. This paper explored percept ion of the owner andpsychological aspects related to debt as source of fund. Samples were the owner of indust ryof fermented soybean cake in Salat iga. The result of this study showed that the owner hadpercept ion that debt was as st imulator. It meant debt encouraged the owner more professionalin f inancial management , work bet ter, more product ive and discipline. The study alsodocumented that overconf idence, illusion of cont rol and availability played important rolein the debt decision.